KITORANG SAMUA BASUDARA: BIJAK BESTARI DI BILIK HARMONI - Abu Muslim (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2016)
This study brings us to see the manifestation of local wisdom of Kitorang Samua Basudara as a patient and adhesion tool for fostering religious harmony in the city of Manado. By utilizing qualitative research approach, this study leads us to conduct studies in three aspects; 1) How is Condition Inter- Religious Harmony in Manado City? 2) What is Local knowledge nuanced harmony in the community? and 3) how is the functioning of the value of local wisdom in caring for religious harmony? Interviews and observations have been selected as data collection method. Then, the nature of the study is descriptive and the theory of multiculturalism is used as a tool of analysis. The results showed that local knowledge of Kitorang Samua Basudara proved as an effective mechanism to maintain and preserve religious harmony in Manado. Having seen the internalization of its values in the public space, the practice of coexistence, and its manifestations in all public institutions is noticeable in the making of religious harmony in Manado. Least but not least, Kitorang Samua Basudara has been present and touched the inner recesses of Manado community, as well as a tool of social control of all kinds of conflict and misunderstanding.